2013
DOI: 10.4049/jimmunol.1300060
|View full text |Cite
|
Sign up to set email alerts
|

CD11chighCD8+ Regulatory T Cell Feedback Inhibits CD4 T Cell Immune Response via Fas Ligand–Fas Pathway

Abstract: Regulatory T cells can restrict the uncontrolled immune response and inflammation, avoiding pathologic immune injury to the host and thus playing important roles in the maintenance of immune homeostasis. Until recently, many subsets of CD4 and CD8 regulatory T cells have been reported. In this study, we identified CD11chighCD8+ T cells as a new subset of CD8+ regulatory T cells. During Listeria monocytogenes and Staphylococcus aureus infection, two subsets of CD8 T cells were classified according to the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 47 publications
(42 reference statements)
3
27
0
Order By: Relevance
“…However, our experimental results obtained in the former studies (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and the present studies have definitely shown the regulatory activity in this T-cell subset. Our current interpretation is that the regulatory and the memory functions are compatible.…”
Section: Cd122supporting
confidence: 56%
See 1 more Smart Citation
“…However, our experimental results obtained in the former studies (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and the present studies have definitely shown the regulatory activity in this T-cell subset. Our current interpretation is that the regulatory and the memory functions are compatible.…”
Section: Cd122supporting
confidence: 56%
“…+ T cells in fact regulates the immune response (28). This is the first report describing that CD8 + Treg cells directly control CD8 …”
Section: Discussionmentioning
confidence: 96%
“…However, in the 40 years since their original description, CD8+ Tregs have been categorized into several distinct phenotypes including: a) Qa-1/HLA-restricted Tregs (5-7); b) CD8+CD122+ Tregs (8); c) CD8+CD28- Tregs (9); d) CD8+Foxp3+ Tregs (10); e) CD8+CD103+ Tregs (11); f) CD8+LAG-3+Foxp3+CTLA-4+ Tregs (12); g) CD8+IL-10+CCR7+CD45RO+ Tregs (13); h) CD8+CD45RC low Tregs (14); i) CD8+CD122+PD-1+ Tregs (15) and j) CD8+CD11c high Tregs (16) (Table 1). CD8+ Tregs can arise within the thymus as naturally occurring CD8+ Tregs or they can be induced in peripheral tissues by a variety of maneuvers including donor-specific transfusion (17), injection of antigen into the anterior chamber (AC) of the eye (18), anti-idiotype immunization with allospecific T cells or MHC-derived peptides (19, 20), or by in vivo immunization combined with blockade of CD40 co-stimulatory molecules (21).…”
Section: Cd8+tregsmentioning
confidence: 99%
“…Contact-dependent suppression by CD8+ Tregs involves the direct killing of CD4+ T effector cells by perforin-mediated cytolysis (25, 26) or FasL-induced apoptosis (16). In addition to suppressing effector T cells, CD8+Foxp3+ Tregs are capable of inducing the de novo generation of CD4+Foxp3+ Tregs by a process that is contact-dependent and requires the production of soluble TGF-β (27), and is reminiscent of a phenomenon that has been previously described as “infectious tolerance”.…”
Section: Cd8+tregsmentioning
confidence: 99%
“…While such tolerance may prevent a potentially harmful inflammatory response to commensal S. aureus , it may also impair effective immune responses to invasion or re-infection. Similarly, a regulatory subset of CD8 + /CD11c hi T cells has been shown to emerge in the setting of S. aureus infection (106). This regulatory subset may inhibit appropriate CD4+ T-cell polarization in response to the organism.…”
Section: The Paradox Of Recurring S Aureus Infectionmentioning
confidence: 99%